Stenalderfund fra Qatar - Kapel, Holger (Kuml, 1964)
Stone Age discoveries in Qatar Qatar is the name of a peninsula which extends from the east coast of the Arabian mainland about 100 miles out into the Arabian Gulf. The greater part of the peninsula is covered by stone and sand desert, interspersed occasionally with flat salt plains -s. sabkha and a few small dumps of bushes and low trees. Northeast of the oil-town Dukhan on the west coast of the peninsula there lies a region of heavily eroded limestone and chalk cliffs. Along the whole of the west coast from Dukhan to Salwa, the Saudi Arabian frontier town, stretches a row of limestone cliffs, reaching a height of about 100 meters above the present sea-level. In the southern part of the country, particularly in the region southwest of the oil-port of Umm Said, there are large areas of wind-blown sand piled up in dunes. At a few points along the east coast and the northern coastal reaches lower cliff formations s.jabal- occur, but the interior of the peninsula consists for the most part of desert of sand and stone without any great physical variation. Politically Qatar is an independent sheikhdom, since 1916 -like the other sheikhdoms along the Trucial Coast- in treaty relations with Great Britain. During the 8 years during which the Danish Archeological Expedition has worked in the sheikhdom, about 200 sites of prehistoric date have been discovered. Of these 141 can be described as Stone-Age sites or as sites with probable connection with Stone-Age cultures. Now that these sites come to be classified half of them immediately have to be disregarded, because they are difficult or impossible to fit into the picture. They comprise a number of small discoveries containing few or uncharacteristic specimens, as well as samples of unworked flint, minerals and the like, which have been collected as material for study in cases where there was a possibility that they might prove to have some connection with the Stone-Age cultures (See the supplementary list p. 145 ff.). There remain 68 sites, which can be roughly divided into four groups: A (of palaeolithic character), B and C (of mesolithic character) and D (of neolithic character). Almost without exception the Stone-Age specimens from Qatar are found on surface sites. The north wind -shamal- blows almost continuously and has raged over the peninsula for millennia, either leaving the Stone-Age specimens exposed on the naked rock surface with no possibility for stratigraphy, or -especially in the southlands- covering extensive areas with immense masses of sand, blown up into colossal, often crescent-shaped dunes -s. barkan- which may well hide beneath them evidence of the wanderings of Stone-Age man in these regions, for the barkans are in the opinion of many geologists of comparatively recent origin. The division into four groups given above, and the archeological definitions of the individual groups, will perhaps not be able to withstand a later scientific investigation of the large body of material collected. For practical reasons, however, it has been necessary to make a classification, and where no weighty reasons have suggested the contrary I have classified the material in accordance with a subjective evaluation of a development from a primitive (macrolithic) flint-working technique with few and simple implement types to a very far from primitive technique with a strongly differentiated inventary of implements dominated by an excellent surface-flaking technique, which produces with equal elegance on the one hand large axes, picks, and spearheads, and on the other small arrowheads and awls of almost microlithic character. It is not my purpose, in this condensed survey of the Stone-Age discoveries in Qatar, to discuss to what degree a gradual development can have taken place on the peninsula from one cultural stage to another, or whether it was rather a question of different peoples or tribes immigrating at longer or shorter intervals. My object is rather to supply a preliminary description and guide to those who may wish to go deeper into the matter. A larger and fully illustrated survey of the material is in the course of preparation, and will probably be ready for publication in the course of a year or two. A sharp distinction between the 4 groups here set up cannot, of course, be drawn. In many cases, too, the various cultures occur mixed on the same sites, which presumably must be interpreted as showing peoples of the various cultures occupying localities suitable for shorter or longer settlement. It has in several cases been difficult for me to decide to which group I should ascribe these mixed discoveries, and it has in these cases been necessary to make a completely subjective decision on the basis of the more obvious cultural characteristics. It is clear that, in a land where the inhabitants to this day understand -and probably occasionally still use- the technique of producing fire by means of flint and steel, mistakes in classification may have crept in. We have several times been in considerable doubt, when we found "human flint" with apparently fresh flaking scars, and our lack of experience made it impossible to decide whether we were looking at the millennia-old swarf of an ancient Stone-Age hunter or the chippings, some few years old, of a wandering modem Bedu. In classification by groups the character and patina of the flint can often be of great assistance. Moreover, the Stone-Age inhabitants of various periods appear to have had preferences for different qualities of flint. The earliest A-cultures appear to have had need for large heavy implements, and have therefore chosen large flint blocks as their raw material, often of a coarse-grained or "spongy" character. We meet with the A-cultures almost without exception upon the highest plateaus (generally of limestone) on many of which enormous quantities of very large and useable flint blocks occur. The "mesolithic" B and C-cultures use for preference a very homogeneous fine-grained flint which is easily flaked. The B-group, which appears to be the earlier of the two, is an almost pure bladeculture. Fine competent tanged arrowheads without barbs are the dominant implement type, and the flint is often chocolate-coloured, very close-grained and uniform in structure. The "chocolate", however, is only a patina; where the implements are recovered from beneath a layer of sand or clay the flint retains its original, almost cream-coloured appearance, a colour which is also revealed by broken pieces of "chocolate-flint." The C-group can be characterised as the scraper-culture group. The flint used is very varied, while the inventory shows a greater number of types than that of the first two groups: awls and points, as well as many small spherical flint blocks, occur, the last-named probably ammunition for slings and the like. It is in the C-group that the first, somewhat clumsily fashioned tanged arrowheads with barbs occur, a type which belongs in the main to the last, D-group. In this D-group, characterised by a surface-flaking technique and an admirable sense of form, the barbed and tanged arrowheads dominate, together with a great number of large and small implements. The typical flake-scrapers of the C-group disappear -and the first true axes appear. In describing the D-group as "neolithic", however, I must make it clear at once that polished axes -or other polished implements- do not occur. Among all the objects discovered in Qatar we have only two specimens of a type of fine greenstone which show signs of polishing. Neither specimen, however, can with certainty be classified as Stone-Age objects, even though there is a high probability that they belong in this catagory, while their shape and appearance give no clue to their function. The flint material in the D-group is very variagated, but the quality and appearance is excellent. A preference seems to have been shown for a veined, agate-like, often reddish-striped flint, which we have called "rose-flint"; but a few sites -probably of early date- exist showing a beautiful, shiny, almost black flint ("desert-polished"). Flaked quartz occurs on many of the sites, particularly those of the C- and D-groups. The fine, carefully fashioned, tanged arrowheads and the other small flint implements are sometimes fashioned of flint of an almost transparent quality, or of a fine smooth quartzite. True microliths do not occur in Qatar. The very few retouched blades which might superficially recall traditional microliths are probably only chance products with a purely coincidental resemblance to deliberately produced microliths. The 68 sites mentioned above divide up as follows into the different groups: Group A (palaeolithic character) 30 sites (I-XXX). Group B (mesolithic blade-arrowhead culture) 8 sites (XXXI-XXXVIII). Group C (mesolithic scraper culture) 19 sites (XXXIX-LVII). Group D (neolithic (?) tanged-arrowhead culture) 11 sites (LVIII-LXVIII). With regard to the following survey of the inventory of the sites it is necessary to remark that in certain cases the term "implements" is used with a conveniently broad margin, insofar as in the few wholly or partly excavated sites all specimens capable of definition (for example as "blades", "scrapers", etc.) are included, while in the case of especially important sites -particularly the palaeolithic (A) sites, characteristic discards are sometimes included as "implements." In the survey the sequence number of the site is given in Roman figures (I-LXVIII), the museum catalogue number in ordinary Arabic numerals preceded by A, and the numbers preceded by Q give the year and sequence of discovery of the site; for example Q.60.14 denotes Qatar expedition-1960-discovery number 14. Two of the implement types in the following tables require more detailed definition, "tile scrapers and knives" and "winged flakes." Tile scrapers (and knives) appear to belong solely to the C and D-cultures, and are fashioned of flat flint "tiles" of natural origin with edge-flaking along one of the edges. They may be flaked either from one or from both sides of the piece, and I have interpreted the specimens with single-sided flaking as scrapers and with double-sided flaking as knives or saws. In order to simplify the table I have not subdivided the "tile" specimens into these two varieties, and the column "tile scrapers and knives" therefore includes both. There is reason to believe that implements of this type have been fashioned and used by the beduin right up to modem times (Fig. 17). The "winged flakes" (Fig. 17) are without exception associated with the D-cultures, they are an unmistakable characteristic of these cultures, and where they are found on the settlement sites of other cultures it must be assumed that they occur through later admixture. They are in practically every case of the transparent or finely figured flint which is typical of the "neolithic" sites with their barbed and tanged arrowheads and surface-flaked implements. The winged flakes should probably be regarded as waste, produced during the making or improving of the cutting edge of axes, picks, or spearheads; but as a few of them appear to have been subjected to a subsequent retouche the possibility cannot be excluded of them having been hafted (with wood or bone) and used as edge-knives or scrapers. Similar implements are known among the Eskimo and other primitive peoples. That the archeological investigations in the sheikhdom have resulted in the collection of such comprehensive and scientifically valuable material is due first and foremost to the exceptional interest and assistance shown to the Danish Archeological Expedition from the very start of its work, not merely by the authorities but also by the Qatar Petroleum Company and by the Shell Company of Qatar. In 1956 the then ruler of Qatar, H.E. Sheikh Ali bin Abdulla AI-Thani graciously gave his permission and assistance to the first preliminary reconnaissance by Professor P. V. Glob and Geoffrey Bibby; and subsequently his successor, H.E. Sheikh Ahmad bin Ali AI-Thani, have hospitably welcomed each year’s expedition team. The Commandant of Qatar’s police and military forces, Ronald Cochrane, has ensured that the various police posts in all districts of the sheikhdom received us hospitably whenever we reached them in our Landrover and had need of their help. Both practically and economically, the support received by the expedition has been so exceptional and so generous that it laid us under an obligation to justify, at some future date, the confidence reposed in us. This article is intended as some slight contribution to this aim. Holger Kapel